The Struggle To Get Freedom In Frank Darabont "The Shawshank Redemption" Movie: An Individual Psychological Approach - Setiawan, Arif; , Drs. Abdillah Nugroho, M. Hum; , Dra. Malikatul Laila, M.Hum (2013)
The main aim's of study is to reveal how the struggle to get freedom from shawshank prison of the major character influences his personality. The objective of this study is to analyze the movie based on the structural analysis and the individual psychological analysis. This study is a qualitative study. The data sources are divided into two, namely primary data source and secondary data source. The primary data is the movie itself, and the secondary data source are the other literatures and virtual references which are relevant to the film. The method of data collection is watching the movie repeatedly, understanding the movie, and uses library research by collecting and selecting the appropriate data from many sources. The technique of data analysis is descriptive analysis by applying the individual psychological approach. Based on the analysis, Andy Defrusneis the reflection of the human trying to get his desire. Frank Darabont wants to describe how human beings have many ways making his dream come true. He also wants to show that human are full of imagination and desire. Andy who always tries to fulfill his wish by struggling and striving to make all dreams become true.